Genomic Variation Landscape of the Model Salt Cress Eutrema salsugineum - Wang, Xiaojuan; Rao, Hua; Ma, Jianxiang; Chen, Xiaodan; Li, Guanglin; Zhao, Guifang (Frontiers in Plant Science, 2021)
Eutrema salsugineum has long been used as the model for examining salt and other abiotic stress in plants. In addition to the forward genetics approaches widely used in the lab, natural variations undoubtedly will provide a rich genetic resource for studying molecular mechanisms underlying the stress tolerance and local adaptation of this species. We used 90 resequencing whole genomes of natural populations of this species across its Asian and North American distributions to detect the selection signals for genes involved in salt and other stresses at the species-range level and local distribution. We detected selection signals for genes involved in salt and other abiotic tolerance at the species level. In addition, several cold-induced and defense genes showed selection signals due to local adaptation in North America-NE Russia or northern China, respectively. These variations and findings provide valuable resources for further deciphering genetic mechanisms underlying the stress tolerance and local adaptations of this model species.